Application Of Heat Coffee Passing Tools With Web-Based Monitoring System: Application Of Heat Coffee Passing Tools With Web-Based Monitoring System - Dede Sunardi; Ritzkal Ritzkal; A Hendri Hendrawan (Jurnal Mantik, 2020)
Coffee not only offers large quantities, but also comes in a variety of qualities, varieties, and shapes. These include arabica and robusta, baked or green, as well as instant and soluble. Coffee exports are also a major source of foreign exchange and national income for many developing countries. In 2012, a total export of 7 million tons contributed a value of US $ 24 billion. Only 10 years ago, the value was only US $ 5.1 billion with a total of 5.5 million tons [2]. in this study contains several problem formulations which consist of (i) How to make hot coffee using RFID. (ii) How to monitor the pouring of hot coffee through the web. The research objectives consist of (i) Designing a tool that can be used to pour hot coffee. (ii) Monitor the hot coffee pourer by web monitoring. The method used in the hot coffee pouring system consists of several, analysis, design, testing, and implementation. So the conclusion of this research is (i) RFID can be made as a request to control the device approved by Arduino Mega 2560. (ii) Web monitoring can display coffee making data by type and time of manufacture.